The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Collaborating across mountains: contributions of the Mountain Invasion Research Network (MIREN) to ecology and conservation - Aníbal Pauchard; Eduardo Fuentes-Lillo; Jake Alexander; Manzoor A. Shah; Agustina Barros; Lohengrin Cavieres; Sylvia Haider; Jonas J. Lembrechts; Keith McDougall; John W. Morgan; Vincent Ralph Clark; Irfan Rashid; et al. (Biological Invasions, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

Endophytic bacterial community composition in wheat (Triticum aestivum) is determined by plant tissue type, developmental stage and soil nutrient availability - Rebekah J. Robinson; Bart A. Fraaije; Ian M. Clark; Robert W. Jackson; Penny R. Hirsch; Tim H. Mauchline (Plant and Soil, 2016)

Developing Policy-Oriented Curricula for Conservation Biology: Professional and Leadership Education in the Public Interest - Tim W. Clark (Conservation Biology, 2001)

Developing Policy‐Oriented Curricula for Conservation Biology: Professional and Leadership Education in the Public Interest - Tim W. Clark (Conservation Biology, 2001)
Some conservation biologists question the ability of current university curricula to prepare students to meet the needs of the profession in solving real‐life conservation problems or to integrate the goals of conservation biology with other societal goals. The gist of the criticism is that curricula tend to emphasize narrow, technical proficiency at the expense of more integrative, “policy‐oriented” problem solving. Conservation biologists' work should be relevant to policy, and I argue that professional participation could become more effective through a broader educational curriculum. Such curricula should teach students three things: (1) an understanding of how the policy‐making system works and how human value interactions constitute the core of professional work, (2) mastery of skills in critical thinking and development of an interdisciplinary, “procedural rationality” for analyzing problems and evaluating potential solutions, and (3) development of influence and responsibility within policy systems. Seminars, case studies, and field trips are among the tools that can develop these skills in students. Finally, the education committee of the Society for Conservation Biology has great potential to improve the quality and relevance of professional education.

Vernal Pool Conservation in Connecticut: An Assessment and Recommendations - Evan L. Preisser; Jennifer Yelin Kefer; Jessica D. Lawrence; Tim W. Clark (Environmental Management, 2000)

Introduction: an Interdisciplinary Effort for Koala Conservation - Steven J. Cork; Tim W. Clark; Nicole Mazur (Conservation Biology, 2000)

Koala Conservation Policy Process: Appraisal and Recommendations - Tim W. Clark; Nicole Mazur; Steven J. Cork; Steve Dovers; Ronnie Harding (Conservation Biology, 2000)
Australia's koalas are a global treasure, yet there is growing concern that present policy may not adequately conserve viable, wild populations in abundant habitats. Problems in the content and particularly the process of policy making for koala conservation include integrating reliable knowledge and diverse perspectives. We reviewed the overall decision process involved in developing Koala conservation policy, including the functions of intelligence, promotion, prescription, invocation, application, appraisal, and termination. To date, intelligence ( planning ) has lacked social science data, and promotion (open debate) has been confrontational. Koala policy has been unclear about prescription (setting rules) and lacks specificity about needed standards, penalties for violating standards, and making resources available. Invocation and application (implementation) have been differentially successful. Appraisal has been adversarial and incomplete, and termination of weak practices has been difficult. We suggest implementation of procedural standards such as timeliness, comprehensiveness, and rationality for a better koala decision process. The 1998 National Koala Conservation Strategy and various state policies can be upgraded to meet these standards. Opportunities exist to improve koala management policy in all seven functions. We recommend a three‐part strategy: (1) identify, describe, and appraise successful conservation efforts to find the best practices, (2) disseminate success stories, and (3) open up new opportunities for improvement in all aspects of koala conservation.

Interdisciplinary Guidelines for Developing Effective Koala Conservation Policy - Tim W. Clark; Nicole Mazur; Robert J. Begg; Steven J. Cork (Conservation Biology, 2000)
Adequacy of the ongoing koala policy process and whether it can conserve koalas is currently in dispute. To address this issue, interdisciplinary guidelines are available to improve koala policy and management and to find consensus. These guidelines focus attention on five policy elements. The first three are rational, political, and moral perspectives on koala policy; the fourth the standpoint of a participant, and the fifth is knowledge integration for practical action. We discuss and illustrate these elements with koala case material. Rationality in policy is addressed through problem orientation, which requires participants to clarify goals, identify problems, and create alternatives in an iterative way. We examined the political dynamics—value clashes—in decision processes. A decision process ideally clarifies and secures common interests. We provide standards for each decision function, such as reliability, comprehensiveness, timeliness. Morality rests on basic premises that are used to justify policy positions. Clarification of the participant's standpoint addresses differing personalities, epistemologies, disciplines, and organizational and parochial biases. Integrating knowledge for practical policy action requires a conceptual framework that is up to the demands of the task. Together the five policy elements make up a logically comprehensive set of interrelated concepts for koala policy development, implementation, and appraisal. Many opportunities exist to use these guidelines skillfully in on‐the‐ground koala conservation efforts to improve koala policy outcomes.

Improving the Evaluation of Conservation Programs - Devra G. Kleiman; Richard P. Reading; Brian J. Miller; Tim W. Clark; J. Michael Scott; John Robinson; Richard L. Wallace; Robert J. Cabin; Fred Felleman (Conservation Biology, 2000)
The evaluation of conservation programs is rare but increasingly important in improving their effectiveness. Regular evaluations of conservation programs and the implementation of recommendations resulting from such assessments are infrequent because of resistance by participants and lack of funding. Evaluations may be internal or external, depending on the purpose of the review and how broadly it is focused. We strongly recommend external peer review of long‐term complex conservation programs every 5 years, supported by more frequent (annual) internal reviews. Criteria for success must encompass both biological and social measures and include learning and the application of new knowledge to management. Evaluations must also go beyond monitoring to assess the value of the program. We emphasize the need to include the organization and function of a conservation program (the process) in any evaluation in addition to substantive criteria for success, which usually involve biological measures (numbers). A dysfunctional program organization and process can as effectively cripple a conservation effort as can a major biological catastrophe. We provide examples of different types of conservation program evaluations, including moderated workshops and case‐study analysis, and provide advice on the logistics and organization of the review, emphasizing the importance of the evaluation process itself to a successful outcome. One important aspect of an evaluation is having an individual with leadership ability and considerable expertise to organize the format and oversee the review process itself. Second, it is essential at the outset to ensure agreement among the program participants and the review committee on the goals and objectives of the conservation program, what is to be evaluated, and the criteria for defining success. Finally, the best evaluations are inclusive and involve all participants and stakeholders.

A Practice‐based Approach to Ecosystem Management - Ronald D. Brunner; Tim W. Clark (Conservation Biology, 1997)
Ecosystem management is a rapidly evolving philosophy or paradigm of natural resource management intended to sustain the integrity of ecosystems. The problem is that principles of ecosystem management are unsatisfactory for practical purposes. Three major approaches to the problem are evaluated: (1) clarification of the goals of ecosystem management, (2) construction of a better scientific foundation for management decisions, and (3) comparative appraisal of current practices. The evaluation concludes that neither of the first two approaches is necessary or sufficient for better management decisions because better decisions depend upon the complexities of particular contexts. The third, practice‐based approach makes the most of the limited human capacity to cope with the complexities of ecosystem management in order to improve principles of ecosystem management, to inform particular management decisions through improved principles, and to incorporate clearer goals and a better scientific foundation as they become available. The evaluation draws on experience and disciplines beyond conservation biology and natural resource management, including policy sciences.